Historical allusions in the Pesharim - O'Donnell, K; O'Donnell, Kevin (1978)
﻿ As the title indicates, this work has two related objectives. The first is to determine whether the literary conventions of the pesher genre deprive the "historical allusions" of any significance. In other words, do the allusions refer to real events and characters, or are they simply symbols or allegories. The second objective follows closely upon the first. Once the historical nature of the allusions is demonstrated, we proceed to investigate the consequences of that demonstration in one specific area: the identification of the three principal characters: the Wicked Priest, the Teacher of Righteousness and the Liar. This work is divided into three parts: Part One: Literary Genre. This section is devoted to the first objective: to determine whether the pesher allusions are in any way historical. Part Two: Information in the Pesharim. Here we list and interpret the references to the Wicked Priest, the Teacher of Righteousness and the Liar found in the commentaries. Part Three: Identification of the Characters. This final section is dedicated to the identification of the three principal characters. The information collected from the pesharim is arranged and compared to what we know about possible candidates from outside contemporary sources. Part One consists of two chapters. The first (The Problems of History in the Pesharim) spells out the problems involved in historical research based on the pesher allusions: has history been subordinated to literary device, and if so, is it possible to determine the extent of this subordination; are the characters individuals, or are they categories, types or titles. There follows upon this exposition of the question, a brief review of the various theories of identification which have been proposed for the Wicked Priest, the Teacher and the Liar. The second chapter (The Effect of Literary Genre on the Pesharim) answers the questions raised in the previous chapter. After analyzing the content, conventions and finality of the pesharim, we conclude that the allusions must refer to known events and characters. The allusions are too fragmentary and basically uninformative to have any meaning or power to convince, if they did not call to mind people and occasions that were well known to the readers. The fact that the readers necessarily had to be well acquainted with the events involved, if they were to make sense of these allusions, does not allow the author to tamper excessively with the historical narrative. Moreover, the very purpose of the whole exercise would be defeated if the author could both re-interpret the texts and falsify the history. He did not tailor 'history to fit prophecy, but rather strained the meaning of the prophet's words to fit the events of the sect's history. The second part begins with a brief introduction which explains the method we shall follow to work out the identity of the principal characters. We then gather all the passages in the pesharim which name them (principally IQpHab, 4QpPssa, and 4QpNah.) We consider as well those places in the Damascus Document where the Teacher of Righteousness and the Liar are mentioned. The third part is divided into three chapters. Chapter Five examines the background of the documents: archaeology, paleography, the identity of the Kittim and the Qumran Community, and finally the single, apparently chronological indication to be found in the scrolls: the three hundred and ninety years in the Damascus Document. We then examine the pesher allusions to the Wicked Priest (Chapter Six) and distinguish between those statements which refer to verifiable facts, and those that merely express the hostility and disapproval of the author. By comparing these statements to information in external contemporary sources (Josephus and the Books of Maccabees) we reach the conclusion that the most likely individual to fit the scroll description of the Wicked Priest is Jonathan Maccabaeus. The texts referring to the Liar are subjected to the same scrutiny, but the results are less satisfying. There is, however, a strong possibility, but only a possibility, that the Liar and the Wicked Priest are the same individual. In that case, Liar would be another name for Jonathan Maccabaeus. Finally we analyze the pesher allusions to the Teacher of Righteousness and compare them to what we know from non-Qumran sources (Chapter Seven.) Although there is abundant information about the Teacher's role in the community, his peculiar teaching, and the esteem in which his followers held him, there is little that points towards his personal identity. Similarly, there is too little information in external sources about those individuals who might be the Teacher of Righteousness to allow us more than random guesses. We can only go so far along truly evidential lines: we can determine a certain period, discover a likely candidate for the Wicked Priest and possibly the Liar, and make certain definite exclusions. Anything beyond this enters the realm of pure conjecture.